Landfill leachate treatment by a combination of a multiple plant hybrid constructed wetland system with a solar photoFenton process in a raceway pond reactor. (1st April 2023) - Spiniello, Ivano; De Carluccio, Marco; Castiglione, Stefano; Amineva, Enzhe; Kostryukova, Natalia; Cicatelli, Angela; Rizzo, Luigi; Guarino, Francesco
Abstract: The sustainable and green treatment of landfill leachate (LL), produced by municipal solid waste, represents one of the most relevant challenges in the integrated waste management systems. Accordingly, in this work a green solution was investigated by coupling an innovative hybrid constructed wetland (HCW) to a solar photo-Fenton (SPF) process. A multiple layers HCW pilot plant including different medium substrates (sand, solid compost and carriers) and plant species ( Phragmites australis, Arundo donax and A. plinii ) was designed. The HCW was functionalised with compost tea solution to simultaneously provide high nutrient content for plants and increase the microorganism biodiversity. Process efficiency was investigated using different real LLs (young and mature) in terms of chemical oxygen demand (COD), nitrogen compounds, chlorides and metals. Removals in the range 75–95% were observed for all the parameters after ten days of leachate recirculation in the pilot plant. Subsequently, the SPF process was carried out in a raceway pond reactor (RPR) as polishing step, significantly improving COD removal (further 49%). HCW combined with SPF in RPR would allow to meet the corresponding limits according to the final use/fate of the effluent by modulating the main parameters of the process. Graphical abstract: Image 1 Highlights: Newly designed constructed wetland was successfully developed for landfill leachate treatment. The hybrid constructed wetland system effectively reduced the target pollutants after 10 days. Optimized conditions of solar photo Fenton were effective as polishing step of leachate after 2.87 kJ L −1 . The purposely designed combination allowed to make the effluent in compliance with the limits for disposal.